Cell‐Penetrating Poly(disulfide) Assisted Intracellular Delivery of Mesoporous Silica Nanoparticles for Inhibition of miR‐21 Function and Detection of Subsequent Therapeutic Effects. (21st June 2016) - Yu, Changmin; Qian, Linghui; Ge, Jingyan; Fu, Jiaqi; Yuan, Peiyan; Yao, Samantha C. L.; Yao, Shao Q.
Abstract: The design of drug delivery systems capable of minimal endolysosomal trapping, controlled drug release, and real‐time monitoring of drug effect is highly desirable for personalized medicine. Herein, by using mesoporous silica nanoparticles (MSNs) coated with cell‐penetrating poly(disulfide)s and a fluorogenic apoptosis‐detecting peptide (DEVD‐AAN), we have developed a platform that could be uptaken rapidly by mammalian cells via endocytosis‐independent pathways. Subsequent loading of these MSNs with small molecule inhibitors and antisense oligonucleotides resulted in intracellular release of these drugs, leading to combination inhibition of endogenous miR‐21 activities which was immediately detectable by the MSN surface‐coated peptide using two‐photon fluorescence microscopy.